1987
DOI: 10.1099/0022-1317-68-1-233
|View full text |Cite
|
Sign up to set email alerts
|

Simian Virus 40-induced Mutagenesis: Action of the Early Viral Region

Abstract: SUMMARYEarlier results have demonstrated a mutagenic activity of simian virus 40 (SV40) in mammalian cells. To analyse this ability further, the effect of SV40 DNA fragments, introduced into Chinese hamster cells, on the frequency of mutations at the hypoxanthine phosphoribosyltransferase locus and other loci was studied. It was found that the mutagenic effect (i) was substantially maintained when the viral genome had been replaced by a fragment comprising the T antigen-coding region and the early promoter--en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Retention of viral sequences was observed in some SV40-induced rodent cell mutant clones [39] (a result which we could not find for a number of BKV-induced mutants tested so far in preliminary experiments). Concerning the mutational mechanism of SV40 activation of error-prone repair processes and/or mutator-like activity of large-T antigen has been discussed [40]. Further work to define the types of mutations that are induced by polyomavirus infection may provide information on the mechanism of mutagenesis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Retention of viral sequences was observed in some SV40-induced rodent cell mutant clones [39] (a result which we could not find for a number of BKV-induced mutants tested so far in preliminary experiments). Concerning the mutational mechanism of SV40 activation of error-prone repair processes and/or mutator-like activity of large-T antigen has been discussed [40]. Further work to define the types of mutations that are induced by polyomavirus infection may provide information on the mechanism of mutagenesis.…”
Section: Discussionmentioning
confidence: 98%
“…It m a y be concluded (i) that the rearrangement which h a p p e n e d in B K V -I R has raised the viral capacity to m u t a t e rodent cells and (ii) that small-t protein activity is not necessarily required for polyomaviruses to be mutagenic. For mutagenicity testing of JC virus, owing to complications connected with preparing highly titered JCV [45] cells were infected with viral D N A as an alternative [40]. As shown in Fig.…”
Section: Mutagenic Activity Of Bkv and Jcvmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have reported no mutagenic effect of SV40 in some experiments and 12-fold or greater increases in the frequency of mutants in other experiments. Conflicting results have been obtained regarding the role of T antigen in SV40-mediated mutagenesis (13,(15)(16).…”
Section: Introductionmentioning
confidence: 99%